Deindustrialization of rural America: Economic restructuring and the rural ghetto. Issue 1 (2nd January 2020) - Green, Gary Paul
ABSTRACT: Since 2000, there has been a significant decline in the number of manufacturing jobs in the US. The manufacturing sector has provided good jobs and benefits, and it has a stronger multiplier effect on regional economies than other industries. Post-industrial theory suggests that there is a natural transition from agriculture to manufacturing, and ultimately, to services. Rural areas, especially those that are small and not adjacent to a metropolitan area, lack the population density and size to support many service sector jobs. Deindustrialization has led to the rise of "rural ghettos." These places face many of the same problems as urban ghettos, such as high levels of underemployment, selective out-migration, social isolation, drug use, and lack of services.